2017
DOI: 10.20471/acc.2017.56.02.02
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON-TB Gold In-Tube Test in the Diagnosis of Latent Tuberculosis Infection in Arthritis Patients Treated with Tumor Necrosis Factor Antagonists

Abstract: SUMMARY -Th e aim of this study was to investigate the role of the QuantiFERON-TB Gold In-Tube test (QFT-GIT) in detecting latent tuberculosis in immunocompromised patients before introducing tumor necrosis factor (TNF-α) antagonists. Th e study included 300 subjects of similar age. Th e study group comprised of 150 QuantiFERON (QFT) positive subjects with rheumatoid arthritis, Crohn's disease, ulcerative colitis, ankylosing spondylitis and psoriatic arthritis, while control group comprised of 150 QFT negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Some limitations to our study include the lack of QuantiFERON test given its high cost. However, although some studies have shown greater sensitivity of this method compared to TST, the difference was not significant in a recent study (27). Second, all patients with a TST conversion received isoniazid, not knowing what would had happened if these patients did not receive the recommended prophylaxis.…”
Section: Discussionmentioning
confidence: 76%
“…Some limitations to our study include the lack of QuantiFERON test given its high cost. However, although some studies have shown greater sensitivity of this method compared to TST, the difference was not significant in a recent study (27). Second, all patients with a TST conversion received isoniazid, not knowing what would had happened if these patients did not receive the recommended prophylaxis.…”
Section: Discussionmentioning
confidence: 76%
“…Çekiç et al, (2015) indicated the percentage of active TB in IBD patients was observed between QFT-GIT and TST results. Positive QFT-GIT test converted to negative in 4% of patients, while QFT negative was not changed[34]. Characteristic of selected studiesAbreu et al (2017) screened LTBI by TST and two different IGRAs assays [QFT-GIT and T-SPOT.TB] in IBD patients under anti-TNF-α therapy for 26 months.…”
mentioning
confidence: 99%